STRATEGIC PASSION AND ITS ROLE FOR ACHIEVING STRATEGIC SUPERIORITY THROUGH STRATEGIC COMPETENCIES - AN INVESTIGATION OF THE OPINIONS OF A SAMPLE STAFF MEMBER IN THE TRADE BANK OF IRAQ (TBI) IN NAJAF - Lect. Dr haider nasser; Lect. Ali sahib flayyih alabachee; Dr. Zaid Abdulzahra Jaffar (Scholars Digest Publishing, 2023)
The current study aims to demonstrate the role that strategic passion can play in achieving strategic superiority through the essential capabilities of organizations. In all aspects of life, the Trade Bank of Iraq in the province of Najaf was adopted as a study community, and the study population reached (225) employees who hold a preparatory certificate or above. The entire community was chosen to reach accurate results, and the programs (SPSS.V.28), (AMOS.V.25) and (Microsoft Excel 2010) were used in the statistical analysis processes, and the study adopted the analytical approach in its research method, and it included three variables The independent variable is strategic passion, and it contains two dimensions (pioneering passion, passion for adventure). The study also adopted three dimensions for the dependent variable strategic superiority (area of influence, competitive pressure, competitive formation), while the intermediate variable had Strategic competencies, five dimensions as well, which are (strategic awareness). Achieving stakeholder goals, organizational change capabilities, administrative capabilities, and problem-solving capabilities). Where the study reached many theoretical and practical conclusions that were conducted on the axes of the study, and by distributing the questionnaire to the respondents, the answers of the researched sample were reached from as the employees of those companies to the availability of strategic passion leading to the development of the strategic superiority of workers through the intermediate variable Strategic competencies.
Keywords: strategic passion, strategic superiority, Strategic competencies, employees of the Trade Bank of Iraq (TBI) in Najaf.